An Investigation of Male Observation Cases That Had Been Charged With Murder to Compare Those Diagnosed With Schizophrenia to Those Diagnosed With Bipolar or Schizoaffective Disorders - Gondwe, Saulos Kalizga (Department of Psychiatry and Mental Health, 2022)
Background The prevalence of violent crime, including murder, is moderately but significantly increased amongst those with severe mental illness compared to the general population. Understanding the characteristics of mentally ill murder offenders may help in the application of evidence-based treatment and rehabilitation strategies. Rationale In the Republic of South Africa (R.S.A), little is known about the characteristics of patients with severe mental illness who are charged with murder. This study has the potential of improving our understanding of these patients. This would subsequently facilitate the development of evidence based interventions in the South African context. Aims The current study aimed to describe the demographic, clinical and criminological characteristics of murder offenders with a diagnosis of schizophrenia or bipolar/schizoaffective disorder and to establish if there are any differences between the two patient groups. Methods Clinical records of male patients diagnosed with schizophrenia or bipolar/schizoaffective disorder following a charge of murder who had been admitted as State patients to the forensic unit of Valkenberg Hospital (VBH) were reviewed. Purposive sampling was used. Data were collected using a questionnaire specifically designed for the study. Those with comorbid intellectual disability (ID) or a neurocognitive disorder and those with missing information were excluded. Ethical approval was obtained from the University of Cape Town, faculty of health sciences human research ethics committee. Results Thirty-seven male patients were included in the study. Twenty-three had a diagnosis of schizophrenia and fourteen had a diagnosis of bipolar/schizoaffective disorder (SCAD). The mean age of the sample was 32.54 years (range: 17-50). Most had a secondary school level of education and were unemployed. There were no sociodemographic differences between the two groups. Persecutory delusions were the most common symptom for both groups (67.57%). The majority of patients had a psychiatric admission prior to the index offence (62.16%). The modal duration of illness for schizophrenia prior to the index offence was less than one year (37.5%) and more than ten years for bipolar/SCAD patients (57.14%). Comorbid personality disorder (PD) was present in 62.5% of the sample. Antisocial PD was the most prevalent. The most commonly used substances were cannabis (70.27%) and alcohol (59.46%). Bipolar/SCAD patients were more likely to use other substances than alcohol or cannabis compared to schizophrenic patients. 89% of the victims were known to the offenders. Family members were victims in 65.2% of the murders. Most of the victims were male (70.27%). Most of the murders occurred at home (75.68%). Schizophrenia patients were more likely than bipolar/SCAD patients to commit the murder at home. Stabbing with a knife was the most common method of murder for both groups (49.45%). Conclusions and Recommendations It can therefore be concluded that patients with schizophrenia or bipolar/SCAD share most demographic, clinical and criminological characteristics which are thought to play a causative role in the commission of murder. Hence, they do not require different rehabilitation strategies. However, general rehabilitation programs for both patient groups should cover several important areas including: social deficits, occupational functioning, substance misuse, treatment adherence and family involvement. Forensic rehabilitation programs should also fully integrate dual diagnosis interventions. Risk assessment and management in both civil and forensic psychiatry services should specifically address persecutory delusions. This should include optimising psychotropic treatment, cognitive behavioural approaches and emphasis on clinicians' duty to warn any potential imminent victims. There should be more robust assessment for comorbid personality disorders as this has a significant impact on the course of illness and the risk for recidivism. In future, a South African multicentre study of similar design should be conducted to increase the sample size and improve the generalisability of the study findings. Future studies should also examine female murder offenders as a separate sample as they may essentially be different from male murder offenders.